HLA polimorphism in the population of Wielkopolska with the consideration of sexes - Kruszyńska, Anna; Przybylski, Zygmunt; Stawarz, Maria (Anthropological Review, 1984)
Studies were performed on 950 unrelated persons, including 653 men and 297 women. Frequencies of HLA-A and HLA-B antigens were estimated for each sex. The frequencies resemble those noted in other European communities.